Robust classification of dental tissues using LIBS data based on data reconstruction and distance prior strategy - Shuting Lin; Xingwei Yi; Lei Yan; Shanshan Liang; Fusong Yuan (Analytica Chimica Acta, 2026)

Pollution prediction of heating boiler plants based on data preprocessing and CNN-LSTM-attention model - Zhengda Lin; Jifeng Wang; Bingjie Yan; Zhe Fu; Liyan Liu; Dan Zhong; Xingwei Du; Jun Zhang (Journal of Environmental Chemical Engineering, 2026)

Multi-time scale energy management and optimization for hybrid power ships considering lifetime balance and extension of multi-stack fuel cell systems - Xiangguo Yang; Xingwei Zhou; Xin Li; Yufan Wang; Fei Long; Telu Tang; Lin Liu; Yifan Liu (Ocean Engineering, 2026)

Magnetic CO2-responsive aerogels with Ag/Fe MOF-derived carbon for adsorption and photo-Fenton-like degradation of organic pollutants - Anrong Yao; Xingwei Fu; Qian Xu; Chang Liu; Yunbo Mo; Qinglan Xue; Jiaojiao Shang; Jianwu Lan; Shaojian Lin (Desalination, 2026)

Hyperspectral BRDF based on UAV measurements can characterize optical properties of flat desert surfaces: A comprehensive comparison with laboratory and satellite data - Yuechao Sheng; Xiuqing Hu; Xingwei He; Lin Chen; Zhongqiu Sun; Shan Lu (Remote Sensing of Environment, 2026)

Synergistically promoting humification and polluting gas reduction in cherry tomato straw composting via carbon bioavailability management - Jiacong Lin; Guangyi Li; Dingmei Wang; Yuqi Pang; Zhuoya Han; Xingwei Meng; Liwen Mai; Shiliang Peng; Qinfen Li (Environmental Pollution, 2025)

A field UAV system (FUAS) with dual spectrometers for BRDF measurement - Xiuqing Hu; Xingwei He; Yuechao Sheng; Na Xu; Lin Chen; Wenjie Hu; Bingcheng Tao; Lu Zhang; Ling Wang; Yuqing He; Zhongqiu Sun (International Journal of Remote Sensing, 2025)

Spatiotemporal variation of forest water conservation based on dual-variable calibration of runoff and evapotranspiration with SWAT model - Jiao Chen; Meiling Zheng; Feng Lin; Xingwei Chen; Huaxia Yao (Agricultural and Forest Meteorology, 2025)

Capacity Estimation of Lithium-Ion Battery Systems in Fuel Cell Ships Based on Deep Learning Model - Xiangguo Yang; Jia Tang; Qijia Song; Yifan Liu; Lin Liu; Xingwei Zhou; Yuelin Chen; Telu Tang (Journal of Marine Science and Engineering, 2025)
The capacity estimation of lithium-ion batteries, serving as an auxiliary power source in fuel cell vessels, is crucial for ensuring system stability and enhancing operational efficiency. Accurate capacity estimation technology not only helps extend battery lifespan but also enhances the energy management and scheduling capabilities of the entire vessel. To address the challenge of accurately estimating lithium-ion battery capacity under complex operating conditions, this study extracts universal health factors from battery data under varied charging and discharging scenarios and combines these with a deep learning model to enhance prediction accuracy. First, battery data from three complex conditions are analyzed, extracting partial charge and discharge data. The distance correlation coefficient calculates the correlation between each factor and the capacity sequence, informing the priority of universal health factors. A TCN-BiGRU model is then developed, with hyperparameters determined by the Kepler optimization algorithm (KOA). Cells from a battery pack under consistent conditions are used for training, while other cells in the same pack serve as the test set. Evaluation metrics include mean absolute error (MAE) and root-mean-square error (RMSE). The testing shows that the MAE and RMSE for full-life capacity estimation remain around 1%, with most cells achieving values under 1%. The results indicate that the proposed method effectively aids in accurate capacity estimation for individual cells in complex operating environments.

Optimization of mechanical properties and finite element simulation analysis of hollow fiber membranes in gas-liquid membrane separation technology - Zhengda Lin; Yihe Wang; Zhe Fu; Dan Zhong; Xingwei Du; Jun Zhang (Desalination, 2025)

Prior Knowledge-Based Two-Layer Energy Management Strategy for Fuel Cell Ship Hybrid Power System - Lin Liu; Xiangguo Yang; Xin Li; Xingwei Zhou; Yufan Wang; Telu Tang; Qijia Song; Yifan Liu (Journal of Marine Science and Engineering, 2025)
Implementing energy management is crucial in the fuel cell and battery or supercapacitor hybrid energy systems of ships. Traditional real-time energy management strategies often struggle to adapt to complex operating conditions; to address this issue and mitigate fuel cell fluctuations during real-time operations while extending the lifespan of lithium-ion batteries, this paper proposes a two-layer energy management system (EMS) based on prior knowledge of ship operation. In the first layer of the EMS, which operates offline, dynamic programming (DP) and low-pass filtering (LPF) are used to allocate power optimally for different typical ship operating conditions. Distribution results are then used to train an SSA-BP neural network, creating an offline strategy library. In the second layer, operating in real-time, the current load power is input into a support vector machine (SVM) to classify the current operating condition. The corresponding strategy from the offline library is then selected and used to provide energy distribution recommendations based on the real-time load and the state of charge (SOC) of the lithium-ion batteries and supercapacitors. The proposed EMS was validated using different ship load cycles. The results demonstrate that, compared to second-order filtering-based real-time energy management strategies, the proposed method reduces fuel cell power fluctuations by 44% and decreases lithium-ion battery degradation by 28%. Furthermore, the simulation results closely align with the offline optimization results, indicating that the proposed strategy achieves near-optimal energy management in real-time ship operations with minimal computational overhead.

Multi-Temporal Energy Management Strategy for Fuel Cell Ships Considering Power Source Lifespan Decay Synergy - Xingwei Zhou; Xiangguo Yang; Mengni Zhou; Lin Liu; Song Niu; Chaobin Zhou; Yufan Wang (Journal of Marine Science and Engineering, 2024)
With increasingly stringent maritime environmental regulations, hybrid fuel cell ships have garnered significant attention due to their advantages in low emissions and high efficiency. However, challenges related to the coordinated control of multi-energy systems and fuel cell degradation remain significant barriers to their practical implementation. This paper proposes an innovative multi-timescale energy management strategy that focuses on optimizing the lifespan decay synergy of fuel cells and lithium batteries. The study designs an attention-based CNN-LSTM hybrid model for power prediction and constructs a two-stage optimization framework: The first stage employs Model Predictive Control (MPC) for long-term power planning to optimize equivalent hydrogen consumption, while the second stage focuses on real-time power allocation considering both power source degradation and system operational efficiency. The simulation results demonstrate that compared to single-layer MPC and the Equivalent Consumption Minimization Strategy (ECMS), the proposed method exhibits significant advantages in reducing single-voyage costs, minimizing differences in power source degradation rates, and alleviating power source stress. The overall performance of this strategy approaches the global optimal solution obtained through Dynamic Programming, comprehensively validating its superiority in simultaneously optimizing system economics and durability.

Removal of antibiotics from aquaculture wastewater using a continuous flow/EC/PMS coupled system - Lulu Long; Jingrong Li; Ting Hou; Min Liu; Yuhuan Lin; Xingwei Zhu; Chao Chen; Gang Yang; Jingsong He (Chemical Engineering Journal, 2024)

PASS4SWAT: Orchestration of containerized SWAT for facilitating computational reproducibility of model calibration and uncertainty analysis - Qiaoying Lin; Dejian Zhang; Jiefeng Wu; Xingwei Chen; Yihui Fang; Bingqing Lin (Environmental Modelling & Software, 2024)

Molecular phylogenetic analysis of the East Asian hemicultrine fishes ( Teleostei: Cyprinidae: Xenocypridinae ), with suggestions to their generic classification and redescription of the recently described species Hemiculter yungaoi Vasil'eva et al. 2022 - Qiaoling Deng; Mingzheng Li; Dan Yu; Lin Chen; Wenjing Li; Xingwei Cai; Huanzhang Liu (Journal of Fish Biology, 2024)
The hemicultrine fishes are a group of small‐sized cyprinids, widely distributed but endemic to East Asian rivers and lakes. Till now, the taxonomic boundaries and relationships within this group remain poorly explored. In the present study, we study the phylogeny of this group, providing suggestions for classification of the hemicultrine group. Using two mitochondrial and three nuclear genes, and samples representing all genera, our results showed that the group consists of seven major lineages, of which four ( Hemiculterella , Hainania , Pseudolaubuca , and Anabarilius ) were monophyletic and three ( Hemiculter , Toxabramis , and Pseudohemiculter ) were not. Based on the phylogenetic tree, we redefined the genera. We revive the genus Siniichthys , which has three species, Siniichthys bleekeri , Siniichthys lucidus , and S. varpachovskii , that were previously treated as members of the genus Hemiculter but showed distant relationships to the genus Hemiculter in our phylogenetic tree. With the new results, a diagnostic key for clades of the hemicultrine group is provided. Furthermore, we provide more detailed information on diagnostic features of the recently described species Hemiculter yungaoi (Vasil'eva et al., 2022). This work will facilitate future systematic studies, pave the way for evolutionary studies, and provide valuable information for the urgent conservation of hemicultrine fishes.

Exploring the impact of malondialdehyde and 4-hydroxy-2-nonena on myofibrillar protein structure: A proteomic analysis - Shichen Zhu; Lin Zhou; Hao Zhu; Xingwei Xiang; Yuanfeng Wu; Yuting Ding; Xuxia Zhou (Food Bioscience, 2024)

Bioenzyme–nanoenzyme–chromogen all-in-one test strip for convenient and sensitive detection of malathion in water environment - Hanwen Zhang; Jiabin Jin; Xini Wang; Wei Han; Lei Qin; Lin Chen; Xiaoyan Mao; Zhenjiang Liu; Xingwei Xiang (Science of The Total Environment, 2024)

Research on satellite data-driven algorithm for ground-level ozone concentration inversion: case of Yunnan, China - Weiqiang Yu; Tao Feng; Xingwei Man; Huan Lin; Haonan Zhang; Rui Liu (Earth Science Informatics, 2024)

Different responses of event-based flood to typhoon and non-typhoon rainstorms under land use change in Xixi Basin of southeastern China - Hong Cheng; Bingqing Lin; Siran Ying; Xingwei Chen; Qingyong Chen; Huaxia Yao (CATENA, 2024)

Triplex visual detection of tobacco potyviruses using reverse transcription recombinase polymerase amplification assay combined with lateral flow dipstick - Tengzhi Xu; Xingwei Lin; Xiaolian Zhang; Yong Fu; Hao Luo; Chun Luo; Zhengduo Luo; Lei Lei; Meng-ao Jia (Crop Protection, 2023)

HMS-REST v1.0: A plugin for the HEC-HMS model to provide RESTful services - Qiaoying Lin; Bingqing Lin; Dejian Zhang; Jiefeng Wu; Xingwei Chen (Environmental Modelling & Software, 2023)

Sulfonated polyhedral oligomeric silsesquioxane-cyclodextrin hybrid polymers for efficient removal of micropollutants from water - Hengye Li; Xingwei Han; Lin Zhang; Wenjie Yu; Wenwen Bie; Meijie Wei; Zhongxia Wang; Fenying Kong; Wei Wang (Carbohydrate Polymers, 2023)

A comparative study on the taste quality of Mytilus coruscus under different shucking treatments - Shichen Zhu; Lin Zhu; Zhigang Ke; Hui Chen; Yadan Zheng; Peng Yang; Xingwei Xiang; Xiaomin Zhou; Youding Jin; Shanggui Deng; Xuxia Zhou; Yuting Ding; et al. (Food Chemistry, 2023)

Synthesis of porous dimethoxypillar[5]arene knitted β-cyclodextrin copolymers for efficient adsorption of organic micropollutants - Hengye Li; Xingwei Han; Wenjie Yu; Lin Zhang; Wenwen Bie; Meijie Wei; Zhongxia Wang; Fenying Kong; Wei Wang (Carbohydrate Polymers, 2023)

Effect of Paecilomyces cicadae polysaccharide Pc0-1 on cyclophosphamide-induced immunosuppression and regulation of intestinal flora in mice - Shiwei Yao; Xingwen Yang; Weijie Wu; Qihong Jiang; Shanggui Deng; Bin Zheng; Lin Chen; Yin Chen; Xingwei Xiang (Food Bioscience, 2023)

Preliminary study of genome-wide association identified novel susceptibility genes for thyroid-related hormones in Chinese population - Liang Huang; Fenghua Bai; Yutian Zhang; Shanshan Zhang; Tianbo Jin; Xingwei Wei; Xiaoli Zhou; Mei Lin; Yufei Xie; Chanyi He; Qi Lin; Tian Xie; et al. (Genes & Genomics, 2022)

Preliminary study of genome-wide association identifies novel susceptibility genes for serum mineral elements in the Chinese Han population - Duojian Guo; Yu Zhou; Xingwei Wei; Shanshan Zhang; Tianbo Jin; Yutian Zhang; Mei Lin; Xiaoli Zhou; Yufei Xie; Chanyi He; Qi Lin; Ping He; et al. (Biological Trace Element Research, 2022)

A comparison of multiplatform wind products in the South China Sea during summer and autumn in 2019 - Yuxin Liu; Mingsen Lin; Xingwei Jiang; Xiujun Sun; Xiangzhou Song (Journal of Oceanology and Limnology, 2021)

Distribution of the early life stages of small yellow croaker in the Yangtze River estuary and adjacent waters - Nan Lin; Yuange Chen; Yan Jin; Xingwei Yuan; Jianzhong Ling; Yazhou Jiang (Fisheries Science, 2018)

Coastal wind field retrieval from polarimetric synthetic aperture radar - Yi Zhang; Xingwei Jiang; Qingtao Song; Mingsen Lin; Xuetong Xie (Acta Oceanologica Sinica, 2014)

Adsorption of fluoranthene in surfactant solution on activated carbon: equilibrium, thermodynamic, kinetic studies - Jianfei Liu; Jiajun Chen; Lin Jiang; Xingwei Wang (Environmental Science and Pollution Research, 2014)

Molecular characterization of a peritrophic membrane protein from the silkworm, Bombyx mori - Xiaolong Hu; Lin Chen; Rui Yang; Xingwei Xiang; Xiaofeng Wu (Molecular Biology Reports, 2013)

Proteomic analysis of peritrophic membrane (PM) from the midgut of fifth-instar larvae, Bombyx mori - Xiaolong Hu; Lin Chen; Xingwei Xiang; Rui Yang; Shaofang Yu; Xiaofeng Wu (Molecular Biology Reports, 2012)

Autographa californica multiple nucleopolyhedrovirus odv-e25 (Ac94) is required for budded virus infectivity and occlusion-derived virus formation - Lin Chen; Xiaolong Hu; Xingwei Xiang; Shaofang Yu; Rui Yang; Xiaofeng Wu (Archives of Virology, 2012)